Research on torsional capacity of composite drive shaft under clockwise and counter-clockwise torque. (21st April 2015) - Hu, Yefa; Yang, Mo; Zhang, Jinguang; Song, Chunsheng; Zhang, Weiming
The design of lay-up has a great influence on the mechanical properties of carbon fiber–reinforced plastic drive shaft. In this research, the stress states of each layer in the carbon fiber–reinforced plastic drive shaft were studied, which were different under opposite torque directions. The Tsai–Wu criterion was used to judge the torsional stability of the composite laminates. The data from finite element analysis showed that torsional capacities of a stacking sequence vary greatly with torque direction, and reasonable lay-up design can reduce the difference. Torque direction should not be ignored when designing a carbon fiber–reinforced plastic drive shaft.